Explicating Choice of MTN® Advertising Frameworks in Nigerian Print Media - Taofeek O Dalamu; Ogunlusi Gbenga (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
The meaning that a communicator intends to make determines the choice of the lexemes that the individual employs. Thus, this study explored the textual choices of MTN advertisements; as such entities were utilised to generate meaning potential. Seven advertisements of MTN functioned as the objects of analysis. The application of Halliday’s Theme-Rheme theoretical lens permitted the processing of the MTN advertisements into various semiotic slots. Such conceptual procedure informed the calibration of the textual components into different frequencies, using the table and graph to demonstrate clearer pictures of the outcomes. Observations showed the kinds of MTN advertising textual choices in two distinct sequences. The first was the thematic choices in the form of marked (As Nigerians, we can weave…), unmarked (Friends are the reason…) and conjunctive logical (so, and, that) constructs. The second aspect was the clause choices available in the texts. These clause choices emanated as declarative (Love is a feeling…), imperative (So reach out) with predicated themes (Share the priceless gift of love), and interrogative (Are you in love?) elements. One could also acknowledge disjunctive grammar (A year of new challenges…) and minor clauses (Happy Valentine’s Day), operating in the communications. Contextually, the study might influence the MTN telecommunications operator to review the nature of textual choices of persuasion, having understood the structures available in the current analysis.